Studies on the Electrical and Optical Properties of Magnesium Phthalocyanine Thin Films - T. G. Gopinathan; C. S. Menon (E-Journal of Chemistry)
Thin films of Magnesium Phthalocyanine (MgPc) are prepared by thermal evaporation technique at a base pressure of 10-5 m.bar on thoroughly cleaned glass substrates kept at different constant temperatures. Films of thickness 2400 A.U. coated at room temperature are subjected to post deposition annealing in air by keeping them in a furnace at different constant temperatures, for one hour. The electrical conductivity studies are conducted in the temperature range 300 K to 525 K. The electrical conductivity is plotted as a function of absolute temperature. The conduction mechanism is observed to be hopping. The thermal activation energy is calculated in different cases and is observed to vary with substrate temperature and annealing temperature. A phase change is observed due to post-deposition annealing at around 523 K. The optical absorption studies are done in the UV-Visible region. The optical band gap energies of the samples are calculated.